2011
DOI: 10.1182/blood-2011-01-330738
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of AL amyloidosis after high-dose melphalan and autologous stem cell transplantation: long-term results in a series of 421 patients

Abstract: Previous studies have suggested that, in patients with AL amyloidosis treated with high-dose melphalan and autologous stemcell transplantation (HDM/SCT), the greatest benefit is seen in those patients achieving a hematologic complete response (CR). We analyzed a series of 421 consecutive patients treated with HDM/SCT at a single referral center and compared outcomes for patients with and without CR. Treatmentrelated mortality was 11.4% overall (5.6% in the last 5 years). By intention-to-treat analysis, the CR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
206
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(224 citation statements)
references
References 34 publications
(46 reference statements)
10
206
0
3
Order By: Relevance
“…However, it is intriguing that the dose of melphalan did not affect OS, contrary to our observation in a series of all amyloid patients, including those with cardiac involvement. 13 Median EFS was 36 months and there was a trend toward shorter EFS in stage III cardiac involvement (33 months) compared with stage I and II (not reached). Univariate and bivariate analysis did not show any statistically significant prognostic variables.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, it is intriguing that the dose of melphalan did not affect OS, contrary to our observation in a series of all amyloid patients, including those with cardiac involvement. 13 Median EFS was 36 months and there was a trend toward shorter EFS in stage III cardiac involvement (33 months) compared with stage I and II (not reached). Univariate and bivariate analysis did not show any statistically significant prognostic variables.…”
Section: Discussionmentioning
confidence: 87%
“…In HDM/SCT, hematologic CR correlates with EFS, OS, cardiac response and reduction in cardiac biomarkers. 7,13 Patients who do not achieve a VGPR or have a less than 90% reduction in serum FLCs exhibit a much worse prognosis. 16,17 In our series, the hematologic CR rate was 27% by intention-to-treat analysis, which compares with 43% in all evaluable patients with AL amyloidosis treated with HDM/SCT in our previous series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20] However, high-dose intensity also is associated with improved disease response. 21,22 Palumbo et al 23 reported improved PFS with melphalan 200 mg/m 2 rather than melphalan 100 mg/m 2 , but increased gastrointestinal toxicity was noted.…”
Section: Indirect Indicators Of Melphalan Pharmacodynamicsmentioning
confidence: 99%
“…1,2 There has been an increasing interest in using induction chemotherapy to cyto-reduce and achieve good hematologic and organ responses prior to AHCT in amyloidosis. 3,4 Bortezomib is a proteasome inhibitor with activity in plasma cell disorders that has been reported to achieve high rates of hematologic and organ response in amyloidosis.…”
mentioning
confidence: 99%